Suppurative Flexor Tenosynovitis: A Case Report - Wibowo, M.D., Pramono Ari; Adnani, Arham ((JOINTS) Journal Orthopaedi and Traumatology Surabaya, 2024)
Background: Suppurative flexor tenosynovitis is an infection of the flexor tendon sheath. This case report presents the clinical course and management of a patient diagnosed with suppurative flexor tenosynovitis. The diagnosis is based on history taking, physical examination, and supporting examination findings. Case Report: A 42-year-old man presented with chief complaints of pain, swelling, and immobility of the index finger of his right hand after being pierced by a fish spine 3 days prior. Physical examination revealed the second digit in a slightly flexed and swollen position, with pain elicited on palpation and passive extension, limiting the patient's range of motion. The patient was diagnosed with suppurative flexor tenosynovitis and treated with antibiotics, debridement, and drainage. Postoperative results were good, with no signs of complications such as spread of infection, tendon necrosis, osteomyelitis, or indications for amputation.Discussion: The treatment for suppurative flexor tenosynovitis involves a combination of antibiotics and surgery. Surgical interventions typically include open drainage and debridement or closed catheter irrigation. Additionally, postoperative rehabilitation is a crucial aspect that requires careful consideration, as it has been shown to accelerate the healing process.Conclusion: Suppurative flexor tenosynovitis is a rare but serious condition that demands early detection and a multidisciplinary approach. Timely surgical debridement and targeted antibiotics, guided by the identification of the causative organism, are essential for positive patient outcomes.